Evaluation of Phytoremediation Potential of Vetiver Grass (Chrysopogon zizanioides (L.) Roberty) for Wastewater Treatment - Mahdi Mahmoudpour; Siamak Gholami; Majid Ehteshami; Marjan Salari (Advances in Materials Science and Engineering)
Water pollution is one of the most critical global issues. Meanwhile, the problem of water pollution of rivers especially in Iran is rising due to expansion of agricultural and industrial applications. Due to a large number of sewer catchments, there are some dam reservoirs like ZHAVE in Iranian state of Kurdistan that have not been able to collect significant amount of water since last 10 years. Removal of heavy metals as contaminants from runoffs and recycling of water is a necessity and a vital issue in the world. Various methods and standards are invented and used to isolate and remove all types of pollutants. This study focuses on the purification and removal of contaminants in water sources using the phytoremediation method by introducing Vetiver grass species in the case of floating treatment wetland (FTW). This study’s preliminary purpose is to investigate a practical remedial solution and improvement methodology for the water quality of reservoirs and rivers by growing the floating Vetiver island method. The results show that following parameters such as COD by 97%, TN by 90%, phosphorus by 66%, TDS by 26%, and evapotranspiration by 40% were reduced. Therefore, we concluded that for a wastewater with varying neutrient concentrations such as in ZHAVE dam, concentration of nutrients N and P was controlled and consequently inhibition and prevention of the eutrophication of water resources in the medium and long term became possible due to reduction in the rate of evaporation from reservoirs.